Makna Komunikasi Keluarga pada Remaja yang Mengalami Ketergantungan Media Sosial: indonesia - Naila Azzahra; Didik Sugeng Widiarto; Nurul Suhesti (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2025)
The increasing dependence on social media among adolescents affects family communication dynamics and the process of constructing self-meaning. This condition highlights the need to understand how family relationships shape adolescents’ digital experiences. This study aims to explore: (1) the meaning of social media for adolescents experiencing digital dependence, (2) the meaning of family in adolescents’ daily lives, and (3) how family communication patterns shape their digital experiences and emotional regulation. This research employs a qualitative phenomenological approach, with five adolescents serving as the main informants and two parents as supporting informants. Data collection was conducted through in-depth interviews and observations of the informants’ daily behaviors. The data were analyzed using thematic analysis techniques by Miles, Huberman, and Saldaña (2014), guided by Koerner and Fitzpatrick’s (2006) Family Communication Patterns Theory to understand the relationship between communication patterns and digital behavior. The findings reveal that social media is perceived as a space for emotional escape, a means of self-regulation, and a platform for identity expression when family emotional support is limited. Family communication patterns were found to influence the intensity of social media use: consensual and pluralistic families provide a sense of security, whereas protective and laissez-faire patterns widen emotional distance and encourage compensatory digital use. These findings underscore the importance of open and responsive family communication in reducing the risk of digital dependence and strengthening adolescents’ emotional well-being.